Analytical Electron Microscopy for Characterization of Fluid or Semi-Solid Multiphase Systems Containing Nanoparticulate Material - Klang, Victoria; Valenta, Claudia; Matsko, Nadejda (Pharmaceutics, 2013)
The analysis of nanomaterials in pharmaceutical or cosmetic preparations is an important aspect both in formulation development and quality control of marketed products. Despite the increased popularity of nanoparticulate compounds especially in dermal preparations such as emulsions, methods and protocols of analysis for the characterization of such systems are scarce. This work combines an original sample preparation procedure along with different methods of analytical electron microscopy for the comprehensive analysis of fluid or semi-solid dermal preparations containing nanoparticulate material. Energy-filtered transmission electron microscopy, energy-dispersive X-ray spectroscopy, electron energy loss spectroscopy and high resolution imaging were performed on model emulsions and a marketed product to reveal different structural aspects of both the emulsion bulk phase and incorporated nanosized material. An innovative analytical approach for the determination of the physical stability of the emulsion under investigation is presented. Advantages and limitations of the employed analytical imaging techniques are highlighted.